Research Trends On Character Education Based On Scopus Database From 2018 To 2023: A Bibliometric Analysis - Sumiharsono, Rudy; Nasaruddin, Nasaruddin; Safrudin, Moh; Ramadhan, Syahrul (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This article presents a bibliometric analysis of research trends in